Nanoparticle-mediated drug delivery to treat infections in the female reproductive tract: evaluation of experimental systems and the potential for mathematical modeling - Sims LB (Dove Medical Press, 2018)
Lee B Sims,1 Hermann B Frieboes,1–3 Jill M Steinbach-Rankins1,3–5 1Department of Bioengineering, University of Louisville, Louisville, KY, USA; 2James Graham Brown Cancer Center, University of Louisville, Louisville, KY, USA; 3Department of Pharmacology and Toxicology, University of Louisville, Louisville, KY, USA; 4Department of Microbiology and Immunology, University of Louisville, Louisville, KY, USA; 5Center for Predictive Medicine, University of Louisville, Louisville, KY, USA Abstract: A variety of drug-delivery platforms have been employed to deliver therapeutic agents across cervicovaginal mucus (CVM) and the vaginal mucosa, offering the capability to increase the longevity and retention of active agents to treat infections of the female reproductive tract (FRT). Nanoparticles (NPs) have been shown to improve retention, diffusion, and cell-specific targeting via specific surface modifications, relative to other delivery platforms. In particular, polymeric NPs represent a promising option that has shown improved distribution through the CVM. These NPs are typically fabricated from nontoxic, non-inflammatory, US Food and Drug Administration-approved polymers that improve biocompatibility. This review summarizes recent experimental studies that have evaluated NP transport in the FRT, and highlights research areas that more thoroughly and efficiently inform polymeric NP design, including mathematical modeling. An overview of the in vitro, ex vivo, and in vivo NP studies conducted to date – whereby transport parameters are determined, extrapolated, and validated – is presented first. The impact of different NP design features on transport through the FRT is summarized, and gaps that exist due to the limitations of iterative experimentation alone are identified. The potential of mathematical modeling to complement the characterization and evaluation of diffusion and transport of delivery vehicles and active agents through the CVM and mucosa is discussed. Lastly, potential advancements combining experimental and mathematical knowledge are suggested to inform next-generation NP designs, such that infections in the FRT may be more effectively treated. Keywords: polymer nanoparticles, 3D cell culture, cervicovaginal mucus, CVM, transport, female reproductive tract, FRT, mathematical modeling, intravaginal delivery